2021
DOI: 10.1182/blood-2021-149644
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Circulating Tumor DNA for Noninvasive Disease Detection, Risk Stratification, and MRD Monitoring in Patients with CNS Lymphoma

Abstract: Introduction: Clinical outcomes for patients with central nervous system lymphoma (CNSL) are remarkably heterogeneous, yet identification of patients at high risk for treatment failure remains challenging with existing methods. In addition, diagnosis of CNSL requires invasive neurosurgical biopsies that carry procedural risks and often cannot be performed in frail or elderly patients. Circulating tumor DNA (ctDNA) has shown great potential as a noninvasive biomarker in systemic lymphomas. Yet, previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Here, the association between ctDNA levels and tumor burden or clinical outcomes is not fully established. For example, while previous studies failed to show any correlation in PCNSL [ 65 , 66 ], Mutter et al recently demonstrated that ctDNA mirrors MRI tumor volumes and predicts PFS and OS, both in log-rank and cox regression analyses, using PhasED-seq for ctDNA quantification [ 68 ]. In FL, three studies targeting either ctDNA clonotypes by IgHTS or assessing cfDNA concentrations by ddPCR revealed significant correlations with baseline TMTV and showed that higher ctDNA/cfDNA levels were associated with shorter PFS [ 38 , 69 , 70 ] (Table 2 ).…”
Section: Technical Considerations For Ctdna Detection and Quantificationmentioning
confidence: 99%
“…Here, the association between ctDNA levels and tumor burden or clinical outcomes is not fully established. For example, while previous studies failed to show any correlation in PCNSL [ 65 , 66 ], Mutter et al recently demonstrated that ctDNA mirrors MRI tumor volumes and predicts PFS and OS, both in log-rank and cox regression analyses, using PhasED-seq for ctDNA quantification [ 68 ]. In FL, three studies targeting either ctDNA clonotypes by IgHTS or assessing cfDNA concentrations by ddPCR revealed significant correlations with baseline TMTV and showed that higher ctDNA/cfDNA levels were associated with shorter PFS [ 38 , 69 , 70 ] (Table 2 ).…”
Section: Technical Considerations For Ctdna Detection and Quantificationmentioning
confidence: 99%
“…A subset of patients with PCNSLs have a good initial radiological response to induction chemotherapy but subsequently have very early disease relapse after consolidative autologous stem cell transplantation. If CSF ctDNA can be used to identify this group before the emergence of radiological evidence of disease relapse, an alternative consolidation therapy, such as whole-brain radiotherapy (for presumed chemoresistant disease), could be offered earlier in the course of disease 84 . Biomarker analyses performed in the context of a phase Ib trial using an NGS panel designed specifically for patients with haematological malignancies were able to demonstrate a positive correlation between a radiological complete response and disappearance of CSF ctDNA, with CSF ctDNA recurrence preceding radiological relapse in one patient 83 .…”
Section: Csf Ctdnamentioning
confidence: 99%
“…63 Cell-free circulating tumour DNA (ctDNA) has recently emerged as a non-invasive prognostic biomarker in patients with lymphoid malignancies 77 and could have a role in cerebral spinal fluid analysis. A recent study 78 of 67 patients with CNS lymphoma (including 12 with isolated secondary CNS lymphoma) identified ctDNA in all cerebral spinal fluid pretreatment samples (100%) and showed a significant correlation of plasma ctDNA concentration with tumour volume and outcomes.…”
Section: Circulating Tumour Dna Analysis In the Cerebrospinal Fluidmentioning
confidence: 99%